COMMUNITY HEALTH ASSISTANCE IN HYPERTENSION CONTROL THROUGH FAMILY EMPOWERMENT AT THE KOMPLEK TALAGO PERMAI KELURAHAN ALAI PARAK KOPI - Ananda, Yuanita; Muliantino, Mulyanti Roberto; Putri, Zifriyanthi Minanda; Muthmainnah; Gusdiansyah, Edo (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2026)
Hypertension is a very important public health issue because it is often referred to as a ‘silent killer’ that does not show symptoms until serious complications arise. This topic was chosen based on the increase in the prevalence of hypertension at the Alai Community Health Centre from the previous year, which shows the urgency of addressing this issue at the community level. The importance of this topic lies in several crucial aspects. First, public awareness of hypertension prevention and management is still low, so many sufferers are unaware of their condition. Second, the role of the family in supporting people with hypertension is not yet optimal, even though the family has a direct influence on the patient's lifestyle, from regulating diet and rest time to medication compliance and regular check-ups. The family is the smallest unit in society that can provide emotional support, motivation, and direct supervision for hypertension management. Empowering families through community health assistance is an effective strategy, as evidenced by the increase in public knowledge from 60% to 100% after education. Therefore, family-based interventions are crucial to improving the quality of life of hypertensive patients and preventing further complications through sustainable lifestyle changes.